2009
DOI: 10.1021/om801053y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zirconium Guanidinate Complexes and the Formation of Zirconium Carbonitride via Low Pressure CVD

Abstract: Thin films of zirconium carbonitride have been deposited on glass at 600°C from two novel guanidinate precursors: [ZrCp′{η 2 -( i PrN) 2 CNMe 2 } 2 Cl] (1) and [ZrCp′ 2 {η 2 -( i PrN) 2 CNMe 2 }Cl] (2) (Cp′ ) monomethylcyclopentadienyl). Both compounds 1 and 2 were structurally characterized by X-ray crystallography. The films grown via low pressure chemical vapor deposition (LPCVD) from compound 1 were mirrorlike with a red-brown sheen whereas those from 2 were gray. Chlorine was present in the films although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…[4][5][6][7] Additionally, we have used silylamines and azides as precursors, which resulted in high quality TiN films, [8][9][10] and this methodology can be extended to other transition metal nitrides. [11] As the understanding of the roles of the precursor have developed, more user-friendly (i.e. safer and easier to handle) precursors have been introduced that have proved capable of not only depositing at much lower deposition temperatures, but also in producing high quality deposits.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Additionally, we have used silylamines and azides as precursors, which resulted in high quality TiN films, [8][9][10] and this methodology can be extended to other transition metal nitrides. [11] As the understanding of the roles of the precursor have developed, more user-friendly (i.e. safer and easier to handle) precursors have been introduced that have proved capable of not only depositing at much lower deposition temperatures, but also in producing high quality deposits.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition of transition metal pnictide thin films is a growing area of research, owing mainly to the useful properties of these films, examples being TiN (Carmalt et al, 2002;Newport et al, 2002), ZrN (Potts et al, 2009), TiP (Blackman et al, 2004), TiAs (Thomas, Blackman et al, 2010), CoAs (Senzaki & Gladfelter, 1994;Klingan et al, 1995) and MnAs (Lane et al, 1994). Such films are often grown by chemical vapour deposition (CVD).…”
Section: Commentmentioning
confidence: 99%
“…As part of recent work into the synthesis of molecular precursors for the deposition of transition metal pnictide thin films (Potts et al, 2009;Thomas, Blackman et al, 2010;Thomas et al, 2011), we recently reported an unusual ligand-exchange reaction between TiCl 4 and As(NMe 2 ) 3 (Thomas, Pugh et al, 2010). The reaction of one equivalent of As(NMe 2 ) 3 with TiCl 4 did not afford the 1:1 adduct [TiCl 4 {As(NMe 2 ) 3 }].…”
Section: Commentmentioning
confidence: 99%